2015 37th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC) 2015
DOI: 10.1109/embc.2015.7318929
|View full text |Cite
|
Sign up to set email alerts
|

On the use of convolutional neural networks and augmented CSP features for multi-class motor imagery of EEG signals classification

Abstract: Learning the deep structures and unknown correlations is important for the detection of motor imagery of EEG signals (MI-EEG). This study investigates the use of convolutional neural networks (CNNs) for the classification of multi-class MI-EEG signals. Augmented common spatial pattern (ACSP) features are generated based on pair-wise projection matrices, which covers various frequency ranges. We propose a frequency complementary feature map selection (FCMS) scheme by constraining the dependency among frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(42 citation statements)
references
References 8 publications
0
42
0
Order By: Relevance
“…Computational intelligence methods have also been used for classification. These include deep learning architectures [5,58,100], as well as RNNs [28], which were previously discussed. Lu et al [101] used a deep neural network constructed using restricted Boltzmann machines and obtained better accuracy than state-of-the-art methods including CSP and FBCSP.…”
Section: Feature Extraction Feature Selection and Classification mentioning
confidence: 99%
See 2 more Smart Citations
“…Computational intelligence methods have also been used for classification. These include deep learning architectures [5,58,100], as well as RNNs [28], which were previously discussed. Lu et al [101] used a deep neural network constructed using restricted Boltzmann machines and obtained better accuracy than state-of-the-art methods including CSP and FBCSP.…”
Section: Feature Extraction Feature Selection and Classification mentioning
confidence: 99%
“…Lu et al [101] used a deep neural network constructed using restricted Boltzmann machines and obtained better accuracy than state-of-the-art methods including CSP and FBCSP. Similarly, using a CNN approach, [58] obtained a better classification performance than a FBCSP approach. Future work may involve comparing the performance of the deep learning classifiers in [58,100] with SVM and LDA classifiers.…”
Section: Feature Extraction Feature Selection and Classification mentioning
confidence: 99%
See 1 more Smart Citation
“…Only recently, DL was also applied to EEG classification. Kumar et al (2016) and Yang et al (2015) suggested replacing commonly used classifiers like SVMs by Multilayer Perceptrons (MLP) while keeping the specialized feature extraction mechanisms. Bashivan et al (2016) used CNNs to classify EEG signals through spectral topography maps generated from short-time Fourier transformed (STFT) recordings.…”
Section: Introductionmentioning
confidence: 99%
“…Kumar et al, 2016 pro-posed an approach for the binary MI-EEG signal classification, that is, right hand and left foot, where the outcomes of the feature extraction stage, which detach the whole procedure from the e2e state, have been applied to the specific type of DDL model, that is, deep neural network. Another type of discriminative DL architecture, that is, convolutional neural network (CNN; Krizhevsky et al, 2012), is exploited by Yang et al, 2015 to classify the multi-class MI-EEG signals composed of four movement tasks, that is, left hand, right hand, both feet and tongue, in a structured manner where the proposed schema includes some different steps such as feature extraction, feature selection, and classification.…”
mentioning
confidence: 99%